Albert Camus, écrivain français d’Algérie - Stępniak, Maria (Studia Romanica Posnaniensia, 2007)
This study is about the Algerianity of Albert Camus, the greatest French writer of Algeria. The topic tackled has three aspects: Algeria as source of work, Camus’s Algerian political philosophy and the deterioration of his relationships with the native Algerian writers. The authoress leads to the following thesis: Albert Camus inscribes himself into the history of North African literature at the decline of the colonial age. His work is situated between a French colonial literature and one of the Algerians, founders of a national literature. Anticolonialist but opposed to the independence of Algeria, Albert Camus was overtaken by the revolution in motion. Camus’s double identity within the context of the Algerian war condemned him to becoming a stranger in his two countries. The drama of his separation fiom the Mother Algeria turned to tragedy with his premature and absurd death. The message of Albert Camus, an agnostic and moralist writer, remains alive. The author of The insurgent man encourages to overtake the absurdity of the human condition by man’s own strengths. Albert Camus, the Algerian sings the wedding of the man and the nature. Great artist, he continues to fascinate generations of readers with his magic word. For some of them, it’s because of its art that the work of Albert Camus remains.